2022
DOI: 10.31219/osf.io/7dbea
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Agentic Playful Teachers: The Playful Mindset of Pre-Service Teachers

Abstract: Play and playfulness are understood as basic and vital elements of early childhood education (ECE), and together with playful pedagogies, they perform a central role in Finnish ECE. In multidisciplinary research, children’s learning is generally understood through the inquiring process of play. However, playfulness, as opposed to play, has received relatively little scholarly attention, and educators’ use of playfulness has received even less (Pinchover, 2017). Playfulness is a vital part of life for both adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As pedagogical experts, playful teachers are adaptive, which in practice means that they are flexible and open to new experiences and not stuck in existing practices and routines. Their pedagogical choices and actions are student-centred instead of teacher-centred or teacher-initiated (Melasalmi et al, 2022), and they trust students and value their opinions. In addition, they are highly engaged in pedagogical and playful learning processes, which leads to students enjoying classes and being satisfied (Kangas et al, 2017).…”
Section: Teachers' Playfulness As a Pedagogical Competencementioning
confidence: 99%
See 1 more Smart Citation
“…As pedagogical experts, playful teachers are adaptive, which in practice means that they are flexible and open to new experiences and not stuck in existing practices and routines. Their pedagogical choices and actions are student-centred instead of teacher-centred or teacher-initiated (Melasalmi et al, 2022), and they trust students and value their opinions. In addition, they are highly engaged in pedagogical and playful learning processes, which leads to students enjoying classes and being satisfied (Kangas et al, 2017).…”
Section: Teachers' Playfulness As a Pedagogical Competencementioning
confidence: 99%
“…Hyvönen, 2008;Kangas, 2010a, b;Kangas et al, 2017;Singer, 2015), the potentials of play and playfulness have also been acknowledged in higher education (Siklander & Harmoinen, 2021;Whitton, 2018;Whitton & Moseley, 2019) and in working life 4 (Bateson & Martin, 2013). Recent studies in early childhood teacher education (ECE) contexts have analysed future ECE teachers' playfulness (Hurme et al, 2022) and playful agency (Melasalmi et al, 2022), which highlight the importance of integrating theoretical and practical learning in education more thoroughly than the current case.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, pre-service teachers emphasized their role as ECE teachers and suggested ways to implement playfulness in ECE teachers' work. The majority of their suggestions were based on teacher-initiated activities, while they were aware of their responsibilities and also concerned about having control over the child groups (Melasalmi et al, 2022). Shin (2022) examined pre-service ECE teachers' perceptions of playful learning, and their reflective reports were analysed qualitatively.…”
Section: Ece Teacher Playfulnessmentioning
confidence: 99%